2022
DOI: 10.1155/2022/9926391
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Sequestration of Cr(VI) from Aqueous Solution Using Biosorbent Derived from Arundo donax Stem

Abstract: The potential of a biosorbent derived from Arundo donax stem, a readily available agricultural product, was examined to remove Cr(VI) from water. Various techniques such as XRD, FTIR, SEM, and EDX were used for the characterization of the prepared adsorbent. The optimal pH for Cr(VI) biosorption was found to be 2.0. The experimental data best suits the Langmuir isotherm model and pseudosecond-order kinetics. The maximum biosorption capacity (qmax) of the investigated biosorbent for Cr(VI) was evaluated to be 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
3
5
0
Order By: Relevance
“…9 , it was determined that the pseudo-second-order model, which had a higher correlation coefficient (R 2 ) value than the pseudo-first-order kinetic model, best explained the adsorption of Cr(VI) onto CPP, suggesting that the Cr(VI) adsorption onto CPP may be driven by chemisorption. The results of the kinetic study were found to align with similar studies conducted previously, that used several biomass-based adsorbents for the adsorption of Cr(VI) ions [ 22 , 23 ]. The calculated kinetic parameter values are shown in Table 2 .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…9 , it was determined that the pseudo-second-order model, which had a higher correlation coefficient (R 2 ) value than the pseudo-first-order kinetic model, best explained the adsorption of Cr(VI) onto CPP, suggesting that the Cr(VI) adsorption onto CPP may be driven by chemisorption. The results of the kinetic study were found to align with similar studies conducted previously, that used several biomass-based adsorbents for the adsorption of Cr(VI) ions [ 22 , 23 ]. The calculated kinetic parameter values are shown in Table 2 .…”
Section: Resultssupporting
confidence: 85%
“…Several methods are being studied and used to eliminate Cr(VI) from the aquatic environment, some of which are ion exchange [ 18 , 19 ], electro-dialysis [ 20 ], redox reaction, membrane technology [ 21 ], and adsorption [ [22] , [23] , [24] ]. Most of the aforementioned solutions can only be used to a certain extent due to the requirement for expensive equipment, incomplete metal removal, hazardous waste sludge, and disposal [ 16 , [25] , [26] , [27] ].…”
Section: Introductionmentioning
confidence: 99%
“…The broad absorption at 3200-3500 cm −1 corresponds to the -OH group of the adsorbent and small absorption band at 2917 cm −1 corresponds to the CH stretching in methylene group. The absorption band around 1704 cm −1 and1610 cm −1 correspond to the C=O and C=C group, respectively [18]. The C-OH stretching band at 1032 cm −1 of RTW got shifted and slightly deformed in CTW which could be associated with the charring process of the material [19].…”
Section: Fourier Transform Infra-red Spectra (Ftir) Analysismentioning
confidence: 96%
“…The result signified that the biosorption of oxyanion of chromium species is favoured at a pH lower than 4.0. Whereas the cationic species are preferably adsorbed at pH conditions above the pH PZC value (Bhattarai et al, 2022;Labied et al, 2018). Figure 5 shows the XRD pattern of the adsorbents.…”
Section: Characterizationmentioning
confidence: 99%
“…Both their raw and modified forms can be used as efficient biosorbents. Our research group has reported several other studies on the Cr(VI) sequestration using different biomass such as pomegranate peels and Arundo donax stem (Bhattarai et al, 2022). The authors hypothesize that litchi seed, an abundant biowaste, also can be modified to an efficient adsorbent for removing pollutants from water.…”
Section: Introductionmentioning
confidence: 99%